Chronic Inflammation in Women with Polycystic Ovarian Syndrome - Işık Üstüner; Murat Sönmezer; Cem Atabekoğlu; Ahmet Ergun; Sevim Güllü; Ruşen Aytaç (Medical Network, 2006)
OBJECTIVE: Our aim was to assess whether C-reactive protein (CRP) which is not only a marker of inflammation but a strong predictor of atherosclerosis and coronary heart disease was increased among women with polycystic ovary syndrome (PCOS). STUDY DESIGN This cross-sectional study was carried out on 18 women with PCOS and 20 healthy subjects matched for body mass index (BMI) and age. Androgenic hormones, anthropometric measurements, metabolic parameters and serum CRP levels were assessed. Further analysis whether there was a correlation between CRP and other parameters was carried out in the PCOS group as well. RESULTS: The androgenic hormones total testosterone (54.51±13.58 vs. 25.0±14.82 ng/dL, p<0.001), and androstenedione (3.7±1.1 vs. 2.78±1.19 ng/dL, p=0.049) were higher in the study group than in control subjects. Dehydroepiandrostenedione sulfate (DHEAS) (191.66±68.79 vs. 179.85±86.32 mg/dL), fasting insulin (15.1±4.1 vs. 14.5±1.7μIu/mL) and postprandial glucose (105±12.7 mg/dL vs. 97.4±10.8 mg/dL) were similar. Fasting glucose was higher in the study group compared to controls (96.1±7.9 vs. 86.6±8.9 mg/dL, p=0.007). Mean CRP levels were higher in patients with PCOS than in healthy controls (1.40±0.98 mg/dL and 0.88±0.39 mg/dL respectiv ely, p<0.001). Regression analysis revealed no correlation between CRP and other factors studied, except for a positive relationship that existed with BMI (r=0.286, p=0.045). CONCLUSION: PCOS patients have increased levels of inf lamation marker CRP which may also signal the tendency to develop cardiovascular disease in addition to established risk factors among PCOS patients.